Intellectual capital and firm performance in India after the companies act, 2013: A study of selected BSE-listed firms - Debnath, Pranesh; Dey, Biplab Kumar; Dey, Moumita; Gachu, Happyson; Lachan, Bitul; Shome, Mihir Kumar (Journal of Social Economics Research, 2023)
This study explores the effect of Intellectual Capital (IC) on the performance of Fast-Moving Consumer Goods (FMCG) and Information Technology (IT) sector firms in India after the Companies Act, 2013. This study used Return on Assets (ROA) as a performance variable. The IC efficiency and its constituents are used as predictor variables and measured by Value Added Intellectual Coefficient (VAICTM) model, which was applied to the longitudinal dataset during Financial Year (FY) 2015-16 to FY 2019-20. The study finds that IC had a momentous affirmative impact on accounting performance during the study period. This study also finds that the components of IC, human capital, and structural capital positively impact firm performance. Nevertheless, this study fails to extract any significant stimulus from the efficiency of physical capital on firm performance. Further, firm experience and size positively influence the performance measured by ROA. This paper highlights new determinants of firm performance, i.e., IC and its components, which market regulators, policymakers, researchers, and investors can take into consideration for different market-related decisions.